BREAST CANCER METASTASIS IN THE STOMACH: WHEN THE GASTRECTOMY IS INDICATED ? - RODRIGUES, Marcus Vinicius Rozo (Arq Bras Cir Dig, 2016)
BACKGROUND: Breast cancer is the most common malignant neoplasm in the female population. However, stomach is a rare site for metastasis, and can show up many years after initial diagnosis and treatment of the primary tumor. AIM: Analyze a case series of this tumor and propose measures that can diagnose it with more precocity. METHODS: Were analyzed 12 patients with secondary gastric tumors. Immunohistochemistry has demonstrated that primary tumor was breast cancer. We retrieved information of age, histological type, interval between diagnosis of the primary breast cancer and its metastases, immunohistochemistry results, treatment and survival. RESULTS: The mean age was 71.3 years (ranging 40-86). Ten cases had already been underwent mastectomy in the moment of the diagnosis of gastric metastasis. Two patients had diagnosis of both primary and secondary tumors concomitantly. At average, diagnosis of gastric metastasis was seven years after diagnosis of primary breast cancer (ranging 0-13). Besides, nine cases had also metastases in other organs, being bones the most affected ones. Immunohistochemistry of the metastases has shown positivity for CK7 antibody in 83.34%, estrogen receptor in 91.67%, progesterone receptor in 66.67% and AE1AE3 antibody in 75%, considering all 12 cases. Moreover, CK20 was absent significantly (66.67%). The positivity of BRST2 marker did not present statistical significance (41.67%). Eight cases were treated with chemotherapy associated or not with hormonal blockade. Surgical treatment of gastric metastasis was performed in four cases: three of them with total gastrectomy and one with distal gastrectomy. Follow-up has shown a mean survival of 14.58 months after diagnosis of metastasis, with only two patients still alive. CONCLUSION: Patients with a history of breast cancer presenting endoscopic diagnosis of gastric cancer it is necessary to consider the possibility of gastric metastasis of breast cancer. The confirmation is by immunohistochemistry and gastrectomy should be oriented in the absence of other secondary involvement and control of the primary lesion.